A Public Law Mechanism for Protecting Citizens from Family Violence - A. V. Ravnyushkin (Сибирское юридическое обозрение, 2024)
The paper examines the problem of family (domestic) violence in the Russian Federation, where a public law mechanism is used to ensure the protection of citizens' rights. Noting that the trends in the development of the system to combat family violence are being discussed in Russian society, the Author indicates that this system should be based on the Russian law and the milieu, i. e. taking into account the traditions and values of Russian society. The paper presents the analysis of public law studies on the functioning legal mechanisms to ensure the rights of citizens to be protected from domestic violence and identify the structural elements of those mechanisms. In particular, the Author defines the properties and elements of the public law mechanism for ensuring the protection of citizens from family violence, and proposes his own definition. The social environment generates a milieu of law and determines the trends in its development. The legal milieu itself is the basis for law-making activities. Due to the adopted or modified legal norms, when they are implemented in various ways over a long period of time, the social milieu also undergoes changes. These changes are viewed as cyclic; however, all the components of this cycle change qualitatively with each turn acquiring new properties. These cycles are directly related to the functioning of public law mechanisms to ensure the rights of citizens are protected. The mechanisms under consideration are dynamic: they themselves are subject to change and they impact certain areas of public relations in order to protecttheir values.   The subject of the study is the norms of constitutional and administrative law, which are the basis for the public law mechanism ensuring the protection of citizens' rights to combat family violence.   The purpose of the study is to formulate the concept of a public law mechanism for ensuring the protection of citizens' rights to combat family violence, to present the mechanism structure, its elements, which can be directions for improving the activities of the subjects of this mechanism.   The functioning of the public law mechanism for ensuring the protection of citizens' rights to combat family violence is based on a set of legal norms, divided by the Author into 4 groups. The following components are among the elements forming the structure of the considered public law mechanism: subjects; instruments; legal and procedural forms of public administration; resources (procurement); a system to observe the legality of the subjects of the public law mechanism for the protection of citizens' rights to combat family violence; criteria and an assessment of the effectiveness and efficiency of the functioning mechanism under consideration.